Periodic splay Fréedericksz transitions in a ferroelectric nematic - Bijaya Basnet; Sathyanarayana Paladugu; Oleksandr Kurochkin; Oleksandr Buluy; Natalie Aryasova; Vassili G. Nazarenko; Sergij V. Shiyanovskii; Oleg D. Lavrentovich (Nature Communications)
Abstract Electric field-induced splay of molecular orientation, called the Fréedericksz transition, is a fundamental electro-optic phenomenon in nonpolar nematic liquid crystals. In a ferroelectric nematic NF with a spontaneous electric polarization $${{\bf{P}}}$$ P , the splay is suppressed since it produces bound electric charges. Here, we demonstrate that an alternating current (ac) electric field causes three patterns of NF polarization. At low voltages, $${{\bf{P}}}$$ P oscillates around the field-free orientation with no stationary deformations. As the voltage increases, the polarization acquires stationary distortions, first splay and twist in a stripe pattern and then splay and bend in a square lattice of +1 and -1 defects. In all patterns, $${{\bf{P}}}$$ P oscillates around the stationary orientations. The stationary bound charge is reduced by a geometrical “splay cancellation” mechanism that does not require free ions: the charge created by splay in one plane is reduced by splay of an opposite sign in the orthogonal plane.